Game performance and intermittent hypoxic training - Hinckson, E. A.; Hamlin, M. J.; Wood, M. R.; Hopkins, W. G. (British Journal of Sports Medicine, 2007)
Live high-train low altitude exposure simulated by hypoxic devices may improve athletic performance. In this study, intermittent normobaric hypoxia was achieved with the GO2altitude® hypoxicator to determine its effects on sea level performance in rugby players. Ten players were randomly assigned to two groups. Players in each group received 14 sessions of either hypoxic (10-15% O2) or normoxic (21% O2) exposure at rest over 14 consecutive days in a single blind fashion. Various performance measures were obtained consecutively in a single testing session pre- and post-exposure. Effects of hypoxic exposure on maximum speed and sprint times were trivial (<1.0%) but unclear (90% likely range, ±5% to ±9%). In rugby simulation, hypoxic exposure produced impairments of peak power in two scrums (15%, ±8%; 9%, ±7%) and impairments of time in offensive sprints (7%, ±8%) and tackle sprints (11%, ±9%). Pending further research, rugby players would be unwise to use normobaric intermittent hypoxic exposure to prepare for games at sea level.